Contribution of cross-links and proteoglycans in intramuscular connective tissue to shear force in bovine muscle with different marbling levels and maturities. (March 2016) - Wang, Fulong; Zhang, Yawei; Li, Junke; Guo, Xiuyun; Cui, Baowei; Peng, Zengqi
Abstract: To explain the factors contributing to the changes in shear force, pyridinoline cross-links and proteoglycans (decorin and glycosaminoglycans) were investigated in longissimus thoracis (LT) taken from Qinchuan steers. In LT muscles with different marbling levels (C, B, A, S) and the same teeth maturity (group I), the contents of cross-links, decorin and glycosaminoglycans (GAGs), as well as the shear force declined gradually with increasing marbling while the collagen heat solubility increased. In group II, the heat solubility gradually declined by 58.22% along with the teeth maturity from 0 to 8 permanent incisors at the same marbling level, whereas the shear force increased by 37.49%. The contents of cross-links, decorin and GAGs increased to 0.72 μmol/g collagen, 34.86 μg/g collagen and 25.46 mg/g collagen respectively. Multivariate statistical results indicated that the shear force was positively correlated with the inherent intramuscular connective tissue traits (content of mature cross-links and proteoglycans) and relied more on the collagen heat solubility than on the content of total collagen. The distribution of the score plots definitely indicated that "youthful and marbled" beef had similar beef characteristics, such as high collagen heat solubility and low shear force. Highlights: Exploration of decreases in cross-links, decorin and GAGs in high marbled beef. Negative correlations were found between IMCT traits and heat solubility. Heat solubility played an important role in determining shear force.